2012
DOI: 10.5923/j.ajbe.20120203.04
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Fully Automated Method for Gridding Microarray Images

Abstract: DNA microarray is a powerful tool and is widely used in genetics to monitor expression levels of thousands of genes in parallel. The gene expression process consists of three stages: gridding, segmentation and quantification. Gridding deals with finding areas in the microarray image which contain one spot using grid lines. This step can be done manually or automatically. In this paper, we propose an efficient and simple automatic gridding method for microarray image analysis. This method was implemented using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…As shown in table 1, the proposed gridding method has high griddingaccuracy values. By comparing the proposed gridding method to other existing methods as those implemented by Deepa J and Tessamma Thomas [28], BasimAlhadidi [29], and Fatma El-ZahraaLabib [30], it was found that the proposed method is more accurate and can grid various types of noisy images correctly as it mainly deals with noisy images. In practice, no method can grid entirely correct.…”
Section: -Low Quality Images (Bad Image)mentioning
confidence: 99%
“…As shown in table 1, the proposed gridding method has high griddingaccuracy values. By comparing the proposed gridding method to other existing methods as those implemented by Deepa J and Tessamma Thomas [28], BasimAlhadidi [29], and Fatma El-ZahraaLabib [30], it was found that the proposed method is more accurate and can grid various types of noisy images correctly as it mainly deals with noisy images. In practice, no method can grid entirely correct.…”
Section: -Low Quality Images (Bad Image)mentioning
confidence: 99%